2005
DOI: 10.1007/s00276-005-0027-2
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical consequences of “open-book” pelvic ring disruption. A cadaver experimental study

Abstract: Open-book fractures create an increase of pelvic volume that facilitates blood diffusion from parietal pelvic vascular network. Ilio-lumbar pedicle seems to be very vulnerable in this type of fracture because of its relations to the sacro-iliac joint and its transversal disposition with regard to this joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 7 publications
3
27
0
3
Order By: Relevance
“…As veins are more fragile than arteries, venous bleeding is always present in addition to an arterial bleed [16,17].…”
Section: Exsanguination Following Pelvic Injuriesmentioning
confidence: 99%
“…As veins are more fragile than arteries, venous bleeding is always present in addition to an arterial bleed [16,17].…”
Section: Exsanguination Following Pelvic Injuriesmentioning
confidence: 99%
“…The retroperitoneal space is a virtual cavity whose ability to accommodate a certain volume of blood depends on the tension generated by the abdominal muscles (intra-abdominal pressure); the hematoma is contained by the abdominal wall and the limited pelvic volume [23]. When the pelvis is fractured, more blood is allowed to collect in the retro-peritoneal space due to the pubic symphysis diastasis: Baquè has showed a diastasis pubic symphysis of 5 cm result in increased pelvic volume of 20.8% [24]; in a similar study, Moos has showed that for every centimeter of diastasis occurs an increase of 4.8% from the same volume [25]. The increase in the volume pelvic determines an increase in bleeding due to the sharp fall of intrapelvic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantages of a management protocol reliant solely on angioembolization include delays due to the relative unavailability of the angiography suite/interventional radiologist and that it does not address venous pelvic bleeding. The contribution of venous hemorrhage to pelvic fracture exsanguination has been recognized in previous cadaveric and clinical studies [55][56][57].…”
Section: Hemorrhage Controlmentioning
confidence: 94%